The ICC Arrest Warrant against Vladimir Putin: Challenges of Prosecuting a Non-Member Head of State for War Crimes in Ukraine - Omida Kazimi (Fakultas Hukum Universitas Islam Indonesia, 2026)
This research examines the ICC arrest warrant issued against Vladimir Putin in connection with Russia's invasion of Ukraine and analyzes the legal and practical challenges the ICC faces in exercising jurisdiction over the head of state of a non-member state. Moreover, this research analyzes the legal basis for ICC jurisdiction on Ukraine, which accepted the jurisdiction of the court under Article 12(3) of the Rome Statute and the principle of the absence of immunity of State officials from international criminal responsibility. The court's dependence on the cooperation of states in executing arrest warrants, the impact of geopolitical considerations on the effectiveness of international criminal justice, are the main political and legal obstacles to prosecuting the head of state of a non-member state. This study, using a descriptive-analytical method in analyzing international law documents, shows that the ICC has legal jurisdiction to investigate crimes committed in Ukraine; political resistance and structural limitations of the international system are the main challenges to exercising this jurisdiction. The arrest warrant for Vladimir Putin is an example of the tension between legal legitimacy and political realities in the application of international criminal justice.